Análise de causalidade da mortalidade das Pequenas Empresas no Brasil - Lima, Ary de Vasconcelos (2009)
The purpose of this study is to analyze the cause of mortality of small companies in Brazil, based on situations economics before and after real plan on 1994, on period between 1995 at 2005, using econometrics resources that aid to identify multiplier and competition characteristics of market, the interrelations between companies births and deaths, and the contrary, to show the diagnoses before and after real implantation. In truth, this study consists on the measure and compare the direction of theses influences, by the corresponding sign of the marginal coefficient, the compatibles graphics demonstrations, considering the real implantation, with the aim, also, of let available to policy makers, of the micro and macro segments, forms of analyze alike situations.